Exploring the Applications of Bio-Eco Architecture for Sustainable Design and Construction process - Naguib,M, M. M.; Hanafi, A. M (European Journal of Sustainable Development, 2013)
It has been commonly noted that the main perception of nature influenced forms isbasically aesthetic while little concern is given to the importance of inspiring from naturein the construction and structural performance of buildings as well as in the naturalecological architectural solutions, thus, this paper will focus on bio-inspired architectureapproach which embraces the eco-friendly practices of sustainable construction, the useof natural materials and the energy conservation by mimicking the natural life.A number of bio-inspired architectural designs will be illustrated presenting acomprehensive analysis of bio-inspired role to be played in developing the concept ofecological sustainable design and construction in contemporary architecture.Building must teach the society with new ecological moral, thus, a better understanding ofbiological morphogenesis can usefully inspire architectural design to resolve challengesthat have already been resolved by nature that will not only help in creating a healthyenvironment but will also produce positive environmental impacts.Bio-Eco Architecture harnesses and replicates the principles found in nature in order tocreate built environment which benefit people and other living creatures as well as safe-guarding the biodiversity; thus, Biomimetics in architecture will help develop a culture ofactive environmental design.